Kualitas Pelayanan dan Kepuasan Melalui Brand Image Terhadap Loyalitas Peserta Diklat Kepelautan - Dian Lieska Ocviany; Annik Mayseptyana; Tatang Suryana; Medy Purwanto (Institut Transportasi dan Logistik Trisakti, 2021)
The purpose of the study was to determine the influence of the factors that influence the quality of service and satisfaction of training participants through the brand image of the marine education and training institution. Methods of research uses quantitative with Path Analysis technique. Path analysis is an extension of regression analysis, to estimate causality between predetermined variables. The results of statistical calculations show that there is an indirect effect of service quality on customer loyalty through Brand Image with a coefficient value of 0.133 and shows that there is an indirect effect of customer quality on customer loyalty through Brand Image with a coefficient value of 0.418. With the results of the study showing the influence of each variable, the service quality affects the satisfaction of the marine training and education institutions, the service quality affects the brand image, the satisfaction affects the brand image, the service quality effects on the loyalty of marine training participants, the brand image affects the loyalty of the marine training participants, the affects the loyalty, the service quality of the marine training and education institutions affects the loyalty of the marine training participants through the brand image.